Potential of on-board colour imaging for in-field detection and counting of grape bunches at early fruiting stages. (1st June 2017) - Abdelghafour, F.; Keresztes, B.; Germain, C.; Da Costa, J. P.
Abstract : In order to enable the wine industry to anticipate in field work and marketing strategies, it is necessary to provide early assessments of vine productivity. The proposed method is designed for the detection and the measurement of grape bunches between the flowering season and the early fruition stages, before 'groat-size'. The method consists of determining the affiliation of a pixel to a grape cluster based on colorimetric and texture features, using an SVM supervised classifier. The eventual affiliation of the pixels is achieved with an average reliability above 75%, which lets us envision in the near future the possibility of estimating the real number of grape bunches.